They Dared for God - Barstad, Glenna; Nang ChanYeema (Mountain View, California USA Pacific Press Publishing Association, 1958)
Short stories include, Joan of Arc, Martin Luther, Florence,William Carey, and Ulrich
Keywords: Adult Nonfiction